PENGARUH KONSELING GIZI TERHADAP KONSUMSI TABLET TAMBAH DARAH DAN KADAR HB PADA IBU HAMIL TRIMESTER II DAN III DI WILAYAH PUSKESMAS II SUMPIUH - RR Titis Pitaloka Djati; Enik Sulistyowati; Heni Hendriyani (Poltekkes Kemenkes Semarang, 2017)
Background : Maternal mortality in 2015, in Banyumas, 21, 14% was caused by bleeding, and one of the causes was anemia. Achievement of blood tablet supplementation of 90 tablets, Banyumas Regency in 2015, has reached 89.26%, but the percentage of anemia pregnant women is still 42%. While Sumpiuh II health center, the achievement of tablet distribution increased blood by 90, already 70, 69%, but anemia pregnant women were still 97, 75%.Objective : To determine the effect of nutritional counseling on blood tablet consumption and Hb levels in second and third trimester pregnant women in the Sumpiuh II Health Center areaMethods : this study included community nutrition research. This type of research, quasi experimental, uses a non-randomized design pre and post control group design. Number of respondents were 20 cases and 20 controls. Data include the amount of blood tablet consumption and Hb levels. Test used, Wilcoxon and paired t test. Whereas to see the effect of counseling on the number of tablets consumed by blood and Hb levels, using Mann Whitney, with a confidence degree of 95%.Results : Pregnant women consumed 100% blood-added tablets before counseling, 42.9%, in the intervention group, and 71.4% in the control group. After counseling, 76.2% in the intervention group and 61.9% in the control group. While Hb levels, before counseling, 38.1% of pregnant women with anemia in the intervention group, and 42, 9% in the control group. After counseling, it became 23, 8%, in the intervention group and 33.3% in the control group.Conclusion : There is an effect of nutritional counseling on blood tablet supplement consumption in second and third trimester pregnant women, in the Sumpiuh II health center area, and there is no effect of nutritional counseling on Hb levels. It is recommended that there be research with different variables to determine the factors that influence the increase in Hb levels